El Cixíido Americano de las palmas, Myndus crudus Van Duzee (Insecta: Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) - F. W. Howard; Sergio Gallo (EDIS, 2007)
EENY-396, a 10-page illustrated fact sheet by F. W. Howard and Sergio Gallo, is the Spanish language version of EENY-389, American Palm Cixiid Myndus crudus Van Duzee (Insecta: Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae). It includes sections on distribution, description, biology, host plants, damage and economic importance, management, and selected references. Published by the UF Department of Entomology and Nematology, October 2006.